PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN PEMIDANAAN PERKARA PEMBUNUHAN DENGAN PELAKU ANAK DALAM PUTUSAN NOMOR 24/PID.SUS-ANAK/2022/PN.BIT - Chacha Feillysita Marsha; Bambang Santoso (Sebelas Maret University, 2026)
This article analyzesthe Judge's Consideration in Rendering a Criminal Judgment in a Murder Case Involving a Child Perpetrator in Verdict Number 24/PID.SUS-ANAK/2022/PN.BIT. The purpose of this article is to examine the conformity of the Judge's consideration in deciding the criminal judgment in Verdict Number 24/Pid.Sus-Anak/2022/PN.Bit with Article 183 of the Indonesian Criminal Procedure Code (KUHAP). This study is normative legal research, with legal sources obtained from primary and secondary legal materials. The author conducted an analysis of Verdict Number 24/Pid.Sus-Anak/2022/PN Bit. The analysis was performed using a major premise based on Article 338 of the Indonesian Penal Code (KUHP) and Verdict Number 24/Pid.Sus-Anak/2022/PN Bit as the minor premise. The legal material collection technique in this research was through literature study, and the legal materials were gathered and processed using the deductive syllogism method. The findings demonstrate that the judge's considerations in imposing a criminal sentence on a child perpetrator in the murder case under Verdict Number 24/Pid.Sus-Anak/2022/PN Bit are in accordance with Law No. 11 of 2012 on the Juvenile Criminal Justice System and Article 183 of KUHAP.